1996
DOI: 10.1016/s0020-7292(96)80003-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, management and outcome in eclampsia

Abstract: Eclampsia is still a serious obstetric complication particularly in uneducated women who do not receive antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
0
11
2
4
Order By: Relevance
“…In the present study the maternal mortality rate was 4.1%, which is nearly 50% lower than previous results at our institute [10]. Other studies have reported mortality rates ranging from as low as 2.9% [17], 3.3% (a population of eclamptic patients who were moribund at admission) [18], 9.5% [19], and 13% [3] to as high as 23.3%. Onuh and Aisien [20] reported a case fatality rate of 10.7% (11 Table 2 Changes in blood pressure after use of nifedipine among the different groups of patients.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In the present study the maternal mortality rate was 4.1%, which is nearly 50% lower than previous results at our institute [10]. Other studies have reported mortality rates ranging from as low as 2.9% [17], 3.3% (a population of eclamptic patients who were moribund at admission) [18], 9.5% [19], and 13% [3] to as high as 23.3%. Onuh and Aisien [20] reported a case fatality rate of 10.7% (11 Table 2 Changes in blood pressure after use of nifedipine among the different groups of patients.…”
Section: Discussioncontrasting
confidence: 66%
“…The incidence of cesarean delivery was 76.7% among all groups in the present study as compared with values of 50.12% to 60% in previous reports [16,19]. At Assiut University Hospital, cesarean delivery is preferred for eclamptic patients.…”
Section: Groupcontrasting
confidence: 44%
See 1 more Smart Citation
“…Nous avons comparé nos résultats à ceux de la littérature (Tableau 6). L'étude de Ducarme et al [8] concernait une maternité de France métropolitaine de niveau IIb, celle de Katz et al [11] deux centres de niveau III de Caroline du Nord, l'étude de Ben Salem et al [19] un centre universitaire de Tunisie et celle de Taner et al [20] un centre médical de référence turc, prenant en charge une population très défavorisée.…”
Section: Discussionunclassified
“…Die Gestose ist eine schwere Komplikation der Schwangerschaft, durch die Mutter und ungeborenes Kind erheblich gefährdet sind [17]. Die Prognose und der Verlauf der Erkrankung sind zudem für den Einzelfall nicht vorhersehbar.…”
Section: Epidemiologie Und Prognoseunclassified